Digital game-based learning: A catalyst for EFL self-efficacy among Indonesian vocational students - Zuhriya, Nurul Aminatus; Sabat, Yuliyanto; Wafiroh, Laili Hibatin (Jurnal Inspirasi Pendidikan, 2026)
While student engagement often is unstable in vocational EFL settings, Digital Game-Based Learning (DGBL) offers a dynamic solution through its interactive framework. This study evaluates how the Wayground platform serves as a catalyst for boosting self-efficacy among Indonesian vocational students. Using a pre-experimental one-group pretest-posttest design, we observed 36 tenth-grade students majoring in Pharmaceutical Engineering at SMK Negeri 1 Sampang (Academic Year 2025/2026). Data collection relied on an EFL self-efficacy questionnaire paired with authentic Wayground activity logs. Statistical analysis was conducted using the Paired-Samples T-test, which indicated a significant increase in self-efficacy (t(35) = -17.955, p < 0.001) with a large effect size (Cohen's d = 2.99). The findings indicate that the use of Wayground-based DGBL is associated with a substantial increase in vocational students' EFL self-efficacy. These results suggest that gamified learning environments may offer a promising pedagogical alternative for fostering self-efficacy among vocational EFL students